Online Social Support for Students Who Are Completing Their Final Thesis Assignments - Sukmawati, Dian; Indira, Zafiera Syafa Putri (Universitas Singaperbangsa Karawang, 2023)
This study aims to determine the form of online social support obtained for students who are completing their final thesis project in the comments of the autobase account @collegemenfess. This type of research is qualitative research using the Netnographic method. Data collection techniques are carried out by online observation, online interviews, and documentation. The results of the research found in the comments of the autobase account @collegemenfess on the final thesis project complaint upload, namely there are five forms of online social support, including, emotional support, appreciation support, instrumental support, information support and social network support. Of the five forms of social support, only three forms of online social support are the most dominant, namely emotional support, instrumental support, and informative support.